Effect of delay in the closed loop control on plants damped - Vargas Tamani, Bruno (2012)
This paper presents a study of the effect of delay in the performance of closed loop systems control plants that can be modeled as second order sobreamortiguadas, in which were not considered the delay in the controller design. They choose the types of plants representative of the second order and are designed for each driver to the classic controller as proportional integral derivative (PID). Experienced with test plants which are conducted previously analog and identification procedures are then controlled by the PID incorporating delays corresponding to plants is not considered in the design. Tests are performed to obtain the corresponding closed-loop performance parameters measured dynamic response to the output of the plant.